Buku petunjuk penyusunan rencana induk pengembangan universitas/institut (Departemen Pendidikan & Kebudayaan, Proyek Pembinaan dan Pengendalian Proyek-Proyek, Direktorat Jenderal Pendidikan Tinggi, 1980)
Handbook for drafting a master plan for the development of universities and institutes of higher education in Indonesia.